Irreducible System of Constraints for a General Polyhedron of Arrangements - Emets, O. A.; Nedobachii, S. I.; Roskladka, О. V. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We construct a system of constraints for a general polyhedron of arrangements that does not contain superfluous inequalities. The derivation of an irreducible system enables one to substantially reduce the number of operations necessary for finding exact solutions of optimization problems on arrangements.